2016
DOI: 10.1016/j.dental.2016.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Filler characteristics of modern dental resin composites and their influence on physico-mechanical properties

Abstract: Mechanical properties and filler characteristics significantly vary among modern RBCs and the current classification does not accurately illustrate either. Further, the chemical stability of RBCs differed, highlighting differences in resin and silane composition. Since E and sorption were well correlated to the filler content, a simple and unambiguous classification based on such characteristic is suggested, with three levels (ultra-low fill, low-fill and compact resin composites).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
163
1
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(194 citation statements)
references
References 46 publications
10
163
1
20
Order By: Relevance
“…The results of mechanical properties are presented in Table . For the methacrylate silane, the smallest filler YBF402 (0.05 μm) had the lowest values of flexural strength, as expected . For thiourethane silane, the highest values were obtained with composites filled with YGB700.…”
Section: Resultssupporting
confidence: 79%
“…The results of mechanical properties are presented in Table . For the methacrylate silane, the smallest filler YBF402 (0.05 μm) had the lowest values of flexural strength, as expected . For thiourethane silane, the highest values were obtained with composites filled with YGB700.…”
Section: Resultssupporting
confidence: 79%
“…The most common classification system for composites considers the distribution and average filler particle size . Based on the classification systems by Lutz and Phillips in 1983, composites can be classified into: macrofilled, microfilled, hybrids, modern hybrids, and nanofilled composites.…”
Section: Composite System Classification Of Dental Compositesmentioning
confidence: 99%
“…Compared to the limited range of shades of the early macrofilled and microfilled composites, modern hybrid composites (0.5–1.0 μm and 10–50 nm) are ideal for esthetic restorations of anterior teeth, because of a variety of different shades with tailored opacity and translucency . Furthermore, with the rise of nanotechnology, nanofilled composites came into being with inorganic phases of characteristic dimensions in the range of 10–100 nm . Because of the increased filler loading and reduced amount of resin matrix, nanofilled composites thereby reduced the polymerization shrinkage while providing esthetics and strength …”
Section: Composite System Classification Of Dental Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent, in depth reviews focusing specifically on the filler technology can be found in the literature [1214], and a summary is provided here. Microfill composites contain colloidal silica particles with average size of 50 nm.…”
Section: The Evolution Of Filler Systemsmentioning
confidence: 99%